Functional analysis of RPS27 mutations and expression in melanoma. (22nd November 2019) - Floristán, Alfredo; Morales, Leah; Hanniford, Douglas; Martinez, Carlos; Castellano‐Sanz, Elena; Dolgalev, Igor; Ulloa‐Morales, Alejandro; Vega‐Saenz de Miera, Eleazar; Moran, Una; Darvishian, Farbod; Osman, Iman; Kirchhoff, Tomas; et al.
Abstract: Next‐generation sequencing has enabled genetic and genomic characterization of melanoma to an unprecedent depth. However, the high mutational background plus the limited depth of coverage of whole‐genome sequencing performed on cutaneous melanoma samples make the identification of novel driver mutations difficult. We sought to explore the somatic mutation portfolio in exonic and gene regulatory regions in human melanoma samples, for which we performed targeted sequencing of tumors and matched germline DNA samples from 89 melanoma patients, identifying known and novel recurrent mutations. Two recurrent mutations found in the RPS27 promoter associated with decreased RPS27 mRNA levels in vitro. Data mining and IHC analyses revealed a bimodal pattern of RPS27 expression in melanoma, with RPS27‐low patients displaying worse prognosis. In vitro characterization of RPS27‐high and RPS27‐low melanoma cell lines, as well as loss‐of‐function experiments, demonstrated that high RPS27 status provides increased proliferative and invasive capacities, while low RPS27 confers survival advantage in low attachment and resistance to therapy. Additionally, we demonstrate that 10 other cancer types harbor bimodal RPS27 expression, and in those, similarly to melanoma, RPS27 ‐low expression associates with worse clinical outcomes. RPS27 promoter mutation could thus represent a mechanism of gene expression modulation in melanoma patients, which may have prognostic and predictive implications.